Fibrillin‐1 Regulates Skeletal Stem Cell Differentiation by Modulating TGFβ Activity Within the Marrow Niche. (17th August 2015) - Smaldone, Silvia; Clayton, Nicholas P; del Solar, Maria; Pascual, Gemma; Cheng, Seng H; Wentworth, Bruce M; Schaffler, Mitchell B; Ramirez, Francesco
ABSTRACT: A full understanding of the microenvironmental factors that control the activities of skeletal stem cells (also known as mesenchymal stem cells [MSCs]) in the adult bone marrow holds great promise for developing new therapeutic strategies to mitigate age‐related diseases of bone and cartilage degeneration. Bone loss is an understudied manifestation of Marfan syndrome, a multisystem disease associated with mutations in the extracellular matrix protein and TGFβ modulator fibrillin‐1. Here we demonstrate that progressive loss of cancellous bone in mice with limbs deficient for fibrillin‐1 ( Fbn1 Prx1–/– mice) is accounted for by premature depletion of MSCs and osteoprogenitor cells combined with constitutively enhanced bone resorption. Longitudinal analyses of Fbn1 Prx1–/– mice showed incremental bone loss and trabecular microarchitecture degeneration accompanied by a progressive decrease in the number and clonogenic potential of MSCs. Significant paucity of marrow fat cells in the long bones of Fbn1 Prx1–/– mice, together with reduced adipogenic potential of marrow stromal cell cultures, indicated an additional defect in MSC differentiation. This postulate was corroborated by showing that an Fbn1 ‐silenced osteoprogenitor cell line cultured in the presence of insulin yielded fewer than normal adipocytes and exhibited relatively lower PPARγ levels. Consonant with fibrillin‐1 modulation of TGFβ bioavailability, cultures of marrow stromal cells from Fbn1 Prx1–/– limb bones showed improper overactivation of latent TGFβ. In line with this finding, systemic TGFβ neutralization improved bone mass and trabecular microarchitecture along with normalizing the number of MSCs, osteoprogenitor cells, and marrow adipocytes. Collectively, our findings show that fibrillin‐1 regulates MSC activity by modulating TGFβ bioavailability within the microenvironment of marrow niches. © 2015 American Society for Bone and Mineral Research.